2014
DOI: 10.7250/msac.2014.002
|View full text |Cite
|
Sign up to set email alerts
|

Providing Quality of Shredded Carrots during Storage by Treatment with Ozonated Water

Abstract: -The objective of the current research is to evaluate the quality changes of shredded carrots treated with 2 ppm ozonated tap water for 60 s ± 1 s. Treated carrots have been packed in several materials (hermetically sealed by breathing polymer film BOPP Propafilm TM P2GAF, cellulose based biodegradable NatureFlex NVS and Polilactid BIO-PLA Containers) and stored at the temperature of + 4 C ± 1 C for 10 days. Main quality parameters using standard methods have been analysed: total carotenoids and β-carotene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Most authors agree that ozone increases the antioxidant activity of the product, some did not find any change, and some reported a decrease in the activity (Table 2). Miller et al [115] for melon, García-Mateos et al [88] for pitaya juice, Glowacz and Rees [143] for chili peppers treated with higher ozone concentration, Auguspole et al [79] for shredded carrots and Karaca et al [61] for parsley leaves observed a decrease in the antioxidant activity. A few more studies have shown that ozone treatment with concentrations up to 1 µmol/mol did not affect the antioxidant activities [59,150].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors agree that ozone increases the antioxidant activity of the product, some did not find any change, and some reported a decrease in the activity (Table 2). Miller et al [115] for melon, García-Mateos et al [88] for pitaya juice, Glowacz and Rees [143] for chili peppers treated with higher ozone concentration, Auguspole et al [79] for shredded carrots and Karaca et al [61] for parsley leaves observed a decrease in the antioxidant activity. A few more studies have shown that ozone treatment with concentrations up to 1 µmol/mol did not affect the antioxidant activities [59,150].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…The form of ozone applied to the product is also very important. Ozonated water is very mildly reactive, and only a single publication shows the negative impact of ozone on the product [79]. In addition to the dose and form of ozone, the method of administration (one time, continuous, or repeatable) also matters.…”
Section: Phenolic Contentmentioning
confidence: 99%
“…The carrot (Daucus carrota L.) is a root vegetable that has world-wide distribution. Carrots are amply consumed in the diet either treated in beverages and meals or fresh (Augspole et al, 2014;Hag, Prasad, 2018;Scarano et al, 2018;Wang et al, 2015). The consumption of carrots, both fresh and processed, has increased due to the introduction of new carrot-obtained health and nutritional goodness (Gamboa-Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The content of oxygen after 12 days inside packaging decreased to 3% on average. ResearcherAugspole et al (2014) in her study noticed that the increase of CO2 inside packaging could indicate the beginning of spoilage process and elevated amounts of CO2 indicate non acceptable quality of packaged shredded carrots. The amount of CO2 increased 11.3 to 15.8 times (Fig.…”
mentioning
confidence: 99%
“…Producing MPV involves cleaning, trimming, peeling, coring, slicing, shredding, washing, etc. (Augspole et al, 2014;Ayhan et al, 2008). Fresh-cut carrots can be found in the market place as: whole peeled (baby), sticks, or sliced, shredded, grated and diced.…”
Section: Introductionmentioning
confidence: 99%